CEMARAN PESTISIDA KLOR-ORGANIK DALAM AIR DANAU BUYAN BULELENG BALI - I. B. Putra Manuaba (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2007)
The use of pesticide around the Lake Buyan is inevitable. This will introduce pollutant to either thesoil or lake water. In this research, organochlorine pesticide residual contamination in water was investigated. LakeBuyan is used as the investigation model, since there were a lot of pressure to the lake as a consequence of increasinghuman activities such as tourism, hotel and restaurant, and farming.This is an expost facto study with Analytical Cross Sectional Study design, within two step activities, i.e.field study in order to gain sampling zone and obtaining sample needed. Followed by laboratory works in order toobtain pesticide residual contamination on water. Sample preparation for this purposed was carried out following astandard method. Gas Chromathographi was employed in order to gain the pesticide contaminant.Positive organochlorine pesticide contaminant, i.e. DDT and chlorotalonile were observed from 55sampling point of water taken from five sampling zones. DDT in the water was 5.02 ppb which is still bellow themaximum level of 42 ppb. Chlorotalonile in water was 1.99 ppb. There is no threshold value of these pesticideresidues on the Government regulation, however, this contamination is still bellow the RfD which is 15 ppb.